Isolasi Bakteri dan Karakterisasi Protease dari Sumber Air Rawa Indralaya - Baehaki, Ace; Rinto, Rinto; Ramiadi, Agus (Jurnal Natur Indonesia, 2012)
The aim of this study was to bacteria isolation and characterization proteases from water swamp. The water swamp samples collected fromIndralaya for microbial isolation. Three isolates showed proteolytic index >1.00. The optimum pH of extraceluller proteases from A6S3,A4S3 and A15S3 were 7.5; 8.0; 8.0, respectively. The optimum temperature of A6S3, A4S3 and A15S3 protease were 40; 50; 50 oC,respectively. Effect of metal ion (Fe, K, Mn, and Zn) shown Fe and K were inhibit protease A6S3, all metal ion were inhibit protease A4S3and K, Mn and Zn inhibit protease A15S3. Study on the effect of metals ion and spesific inhibitors indicated that all protease weremetaloprotease. Their moleculer weights were determined by using SDS-PAGE and zymogram technique for A6S3 isolate were 70, 88, 106and 121 kD respectively. Whereas for isolate A4S3 was 138 kD and isolate A15S3 was 131 kD.